Neuroimaging endpoints in amyotrophic lateral sclerosis - Menke, R; Agosta, F; Grosskreutz, J; Filippi, M; Turner, M (Springer Verlag, 2016)
Amyotrophic lateral sclerosis (ALS) is a progressive neurodegenerative, clinically heterogeneous syndrome pathologically overlapping with frontotemporal dementia. To date, therapeutic trials in animal models have not been able to predict treatment response in humans, and the revised Amyotrophic Lateral Sclerosis Functional Rating Scale (ALSFRS-R), which is based on coarse disability measures, remains the gold standard measure of disease progression. Advances in neuroimaging have enabled mapping of functional, structural and molecular aspects of ALS pathology, and these objective measures may be uniquely sensitive to the detection of propagation of pathology in vivo. Abnormalities are detectable before clinical symptoms develop, offering the potential for neuroprotective intervention in familial cases. Although promising neuroimaging biomarker candidates for diagnosis, prognosis and disease progression have emerged, these have been from the study of necessarily select patient cohorts identified in specialized referral centres. Further multi-centre research is now needed to establish their validity as therapeutic outcome measures.